LARVACIDAL ACTIVITY OF EXTRACT AND ESSENTIAL OIL OF CURCUMA MANGGA RHIZOME (Curcuma mangga VAL.) AGAINST LARVAEAedesaegypti - Dudi Runadi (Universitas Bhakti Kencana, 2015)
Dengue Hemorrhagic Fever (DHF) causedby Aedesaegypti is a pestilentdisease. Many people commonlyuselarvacidefromthehazardous syntheticmaterials for preventingthis disease.In this study, larvacidal activity of ethanolextractandessential oil of Curcuma mangga rhizome was investigated.Test solutions prepared by diluting each extract and essential oil in order to obtain100 µg/mL, 50 µg/mL, 10 µg/mL, 5 µg/mL, 1 µg/mL and 0.5 µg/mLconcentrations in 100 ml water.Larvae Aedesaegyptiinstar 3-4 were used in this study.The results of larvacidal test showed that the extract of Curcuma mangga rhizome was not significantly performed the larvacidal activity, whereas the essential oil of Curcuma mangga significantly performed the larvacidal activity with the values of LC50 as 61.025 µg/mL.